2023
DOI: 10.1177/00368504231165679
|View full text |Cite
|
Sign up to set email alerts
|

Green supply chain transformation and emission reduction based on machine learning

Abstract: Artificial intelligence techniques provide more possibilities for supply chain transformations in the face of global warming and environmental degradation. This study examines the Cournot game model of two competing supply chains with various carbon emission technologies as well as the possibility of upgrading machine learning technology. The investment risk of a supply chain's technology upgrade is either symmetric or asymmetric information. In the case of symmetric information, results show that the machine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In the following paper, Wu and Zuo 12 consider whether AI techniques provide more possibilities for supply chain transformation to overcome the adverse effects of global warming and environmental degradation. A Cournot game model with an upgrading ML technology is employed to evaluate the use of green technologies of two competing supply chains.…”
Section: Contributions Of Collectionsmentioning
confidence: 99%
“…In the following paper, Wu and Zuo 12 consider whether AI techniques provide more possibilities for supply chain transformation to overcome the adverse effects of global warming and environmental degradation. A Cournot game model with an upgrading ML technology is employed to evaluate the use of green technologies of two competing supply chains.…”
Section: Contributions Of Collectionsmentioning
confidence: 99%
“…By comprehensively understanding and implementing these factors and dimensions, businesses can mitigate environmental impact and gain a competitive edge in the market. Wu and Zuo [ 29 ] investigated the Cournaud game model involving two competitive supply chains with different carbon emission technologies and the potential for improving machine learning technology. The findings revealed that the market equilibrium generated by the duopoly model remained unaffected by the threat of machine learning technology upgrades.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The use of AI technology can improve energy efficiency and reduce resource waste, thereby realizing low carbon development [15]. In addition, AI technologies provide more opportunities for traditional supply chains to transition to green supply chains by reducing carbon emissions [16]. However, scholars have opposing views on this topic.…”
Section: Introductionmentioning
confidence: 99%